2017
DOI: 10.24036/sjdgge.v1i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Carbon Absorption and Economic Benefits in Various Scenarios of Community Forest (HKm) Land Management Through The Scheme of Plan Vivo in The Upstream Watersheds (DAS) of Renggung River, Central Lombok Regency, Indonesia

Abstract: This study aims to (1) estimate carbon absorption and the economic benefits of HKM land management through Plan Vivo scheme and (2) determine the composition of plants to be prioritised. This research was conducted in the upstream watershed of Renggung River in Central Lombok. The calculation of the estimated carbon absorption was obtained using allometric equations, while the estimated economic benefits were calculated from the production of commodities that are grown and the potential of carbon trading. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The vegetation density of communitymanaged forest areas, especially on the island of Lombok, has become an important concern because it is one of the references in payment for carbon environmental services. Sukardi et al [46] reported that Aikbual community forest farmers in Lombok Island participated in the development of the Plan Vivo scheme of environmental services by adding 290 multipurpose and forestry crops per ha so that the tree population in the managed land was 400 trees per ha. The basal area of the stand at the study site is presented in Table 5.…”
Section: No Species Tp1 Tp2 Tp3 Tp4mentioning
confidence: 99%
“…The vegetation density of communitymanaged forest areas, especially on the island of Lombok, has become an important concern because it is one of the references in payment for carbon environmental services. Sukardi et al [46] reported that Aikbual community forest farmers in Lombok Island participated in the development of the Plan Vivo scheme of environmental services by adding 290 multipurpose and forestry crops per ha so that the tree population in the managed land was 400 trees per ha. The basal area of the stand at the study site is presented in Table 5.…”
Section: No Species Tp1 Tp2 Tp3 Tp4mentioning
confidence: 99%
“…Water has an important role as a basic need that must be met for human survival [1,2]. The need for water to meet population activities is increasing, apart from the increase in population, also because activities that require water increase, such as industrial areas, trade, education, tourism, and so on [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, this research must be carried out with the objectives of: (1) identify the community's willingness to pay (WTP) for domestic water environmental services and their WTP value; (2) analyze the factors that influence the WTP value for domestic water; (3) analyze the potential for selffinancing for water conservation; and (4) formulate mechanisms and strategies for managing conservation selfhelp funds.…”
Section: Introductionmentioning
confidence: 99%
“…Land management is currently focused on the concept of sustainable land management. Sustainable land management paradigm implies that in meeting the needs of our current, current management trends should not diminish the ability of natural resources to meet the needs of future generations (Sukardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%